The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1128/aac.00551-07
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Double-Blind, Randomized Trial of Ceftobiprole Treatment of Complicated Skin and Skin Structure Infections Caused by Gram-Positive Bacteria

Abstract: Ceftobiprole is the first broad-spectrum cephalosporin with activity against methicillin-resistant Staphylococcus aureus (MRSA) to be assessed in late-stage clinical trials. As a pivotal step in the clinical development of ceftobiprole, a multicenter, global, randomized, double-blind trial was conducted to compare the efficacy of ceftobiprole to that of vancomycin in patients with complicated skin and skin structure infections (cSSSIs) caused by gram-positive bacteria. The primary objective was to assess nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
137
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 25 publications
6
137
1
Order By: Relevance
“…a These numbers correspond to 2 different randomized controlled trials that were published as one in Clinical Infectious Diseases. 50 45 2005 Corey et al, 39 2010 D'Antonio et al, 55 2004 Florescu et al, 44 2008 Gilbert et al, 72 1991 Jaksic et al, 32 2006 Kureishi et al, 69 1991 Lin et al, 27 2008 Noel et al, 43 2008 Noel et al, 42 2008 Rolston et al, 66 1994 Rolston et al, 58 1999 Rubinstein et al, 38 2001 Rubinstein et al, 50 2011 (0015) …”
Section: Discussionmentioning
confidence: 99%
“…a These numbers correspond to 2 different randomized controlled trials that were published as one in Clinical Infectious Diseases. 50 45 2005 Corey et al, 39 2010 D'Antonio et al, 55 2004 Florescu et al, 44 2008 Gilbert et al, 72 1991 Jaksic et al, 32 2006 Kureishi et al, 69 1991 Lin et al, 27 2008 Noel et al, 43 2008 Noel et al, 42 2008 Rolston et al, 66 1994 Rolston et al, 58 1999 Rubinstein et al, 38 2001 Rubinstein et al, 50 2011 (0015) …”
Section: Discussionmentioning
confidence: 99%
“…It has been assessed in clinical trials involving patients with complicated skin and skin structure infections (cSSSI), including those caused by methicillin-resistant Staphylococcus aureus (MRSA) (15,16). In one of these trials, which was conducted with patients with cSSSI due to gram-positive and/or gram-negative pathogens, ceftobiprole at 500 mg every 8 h administered as a 2-h infusion was statistically noninferior to a combination of vancomycin plus ceftazidime (15).…”
mentioning
confidence: 99%
“…Finally, two 5 th generation cephalosporin prodrugs (ceftaroline fosamil and ceftobiprole medocaril) have been found to possess anti-MRSA activities. Ceftaroline has been shown to produce similar clinical cure rates as vancomycin in complicated skin and skin structure infections (Iizawa, Nagai et al 2004;Ge, Biek et al 2008), whereas ceftobiprole was found to show similar efficacy as vancomycin in suspected gram positive infections, diabetic foot and mixed bacterial complicated skin and skin structure infectons (Noel, Bush et al 2008 a;Noel, Strauss et al 2008;Noel, Strauss et al 2008 b). In summary, several newer antibiotics have been shown to provide a potential equally effective but less nephrotoxic alternative to vancomycin for deep-seated MRSA infections.…”
Section: Discussionmentioning
confidence: 99%